Current Diagnosis & Treatment in Psychiatry - Michael H. Ebert, MD , Peter T. Loosen, MD, PhD Barry Nurcombe, MD (McGraw-Hill, 2000)
Current Diagnosis & Treatment in Psychiatry reflects the current dynamic state of psychiatric knowledge. New discoveries from the basic biomedical and psychological sciences are having a major impact on psychiatric practice today. The task is to translate these new discoveries into a form useful to clinicians. This text is intended to be practical, succinct, and useful for all health care professionals who encounter and provide care for individuals with psychiatric symptoms and behavioral disturbance.